Developing a Leadership Skills Framework as a Tool for motivating construction managers in the Anambra State (British Journal of Multidisciplinary and Advanced Studies, 2023)
Developing a framework is having a standard metric or structure for investing these developmental incentives into the chief work influencers “construction managers”. The importance of adopting a leadership Skill framework that contains development and growth metrics cannot be over-emphasized; it starts the system of energizing construction managers with the requisite leadership capacity to help organizations achieve project targets, sustains project performance, administers technical expectations, manages stakeholders, eliminates disputes, enables indigenous contractor’s success on a global scale as well as serve as a personal development avenue. The study aims to develop a leadership skill framework as a Tool for motivating construction managers in the Anambra State. To achieve this, the study identifies what to consider in choosing a Leadership Management Development Approach and examines certain developmental strategies in developing a robust leadership skills Framework for Construction Managers Motivations. The study adopted descriptive survey design by distributing 60 well-structured questionnaires. The 40 retrieved and analyzed responses (table 3.1) shows that extracted components value have Eigen value of 8.981, 2.228,1.683,1.362 and 1.167 with associated percentage variance of about 44.903% ,11.142%,8.415%,6.809 % and 5.833 % respectively which summed up to 77.1% showing that the extracted leadership skills can explain over 77.1% of the total variance in the series. The 6th to 20th leadership skills have Eigen value below 1.000 and jointly explain only about 22.9% of the total variations which confirm that they are no necessity important for considerations. The component matrix in table 3.1 shows that the choice of the leadership skills like Communication was extracted in component 1, Planning for the Required Result in component 2, Flexibility in component 3, Risk-Taking in component 4 and Focusing on Process in component 5 out of the identified leadership skills. The study recommends that the developed leadership skills framework is for construction stakeholders and is used as a motivational tool for construction managers in Anambra State to increase productivity and retention of construction employees. When developing construction managers in Anambra State, the human resources team should prioritize communication skills, the ability to plan for the desired outcome, flexibility in decision-making, the ability to take risks, and a focus on the work process rather than the output.